Penerapan Scientific Crime Investigation dalam Mengungkap Tindak Pidana Pembunuhan Pada Tingkat Penyidikan - Ulia Tirafike Arbalen; Maya Shafira; Muhammad Farid; Ahmad Irzal Fardiansyah; Nikmah Rosidah (Media Hukum Indonesia (MHI), 2026)
This study analyzes the application of the Scientific Crime Investigation (SCI) method in the investigation of murder cases at the investigation level as per Decision Number 425/Pid.B/2024/PN Mgl. This case faced obstacles due to the lack of witnesses and evidence, making conventional investigations difficult. The research method used a normative juridical approach supported by an empirical approach. Data was obtained through literature studies and interviews with investigators and lecturers, then analyzed qualitatively. The results of the study show that the application of SCI is carried out through three main areas, namely identification, forensic medicine, and forensic laboratories. Forensic medicine through visum et repertum and forensic laboratories through DNA testing have significant revelatory power in connecting the perpetrator with the victim. However, the application of SCI still faces obstacles in the form of limited forensic facilities, a lack of human resources, weak coordination between agencies, and low public awareness in preserving crime scenes.